The world is your oyster: low-dose, long-term microplastic exposure of juvenile oysters - Maes Thomas; Barry Jon; Stenton Craig; Roberts Edward; Hicks Ruth; Bignell John; Vethaak A. Dick; Leslie A. Heather; Sanders Matthew (Heliyon, 2020)
Bivalve filter feeders, such as oysters, filter large volumes of water and are particularly exposed to microplastics (MP). Consequently, these animals digest and assimilate high levels of MP in their bodies that may likely impact their physiology, and potentially affect shellfish stocks, benthic habitats and, indirectly, the health status of the marine ecosystem and human consumers. In this study we exposed juvenile oysters, Crassostrea gigas, to 3 different MP concentrations (104, 105 and 106 particles L−1), represented by 6μm Polystyrene (PS) microbeads, compared to a control treatment receiving no MP. The study ran for a period of 80 days to test for the impacts of MP on growth, Condition Index and Lysosomal Stability. From histological analysis, microbeads were detected in the intestines of exposed oysters and in the digestive tubules, but no cellular inflammatory features were observed over time. Weight and shell length remained comparable between the different treatments and control. We found that Condition Index in the highest concentration increased initially but significantly reduced over time. The oysters in the highest MP exposure also showed the lowest mean Lysosomal Stability score throughout the experiment. Lysosomes play a vital role in the cells defense mechanisms and breakdown of constituents, crucial for the oysters’ wellbeing. Most importantly, we detected an increased mortality in those oysters who were chronically exposed to the highest loads of MP.